The Stem Sap Flow and Water Sources for Tamarix ramosissima in an Artificial Shelterbelt With a Deep Groundwater Table in Northwest China - Liu, Feiyao; You, Quangang; Xue, Xian; Peng, Fei; Huang, Cuihua; Ma, Shaoxiu; Pan, Jing; Shi, Yaofang; Chen, Xiaojie (Frontiers in Plant Science, 2022)
The shelterbelt forest between oases and the desert plays a vital role in preventing aeolian disasters and desertification in arid regions of northwest China. Tamarix ramosissima (T. ramosissima), a typical perennial and native xerophyte shrub in Northwest China, grows naturally and is widely used in building artificial shelterbelt forests. The balance between water consumption and the availability of water determines the survival and growth of T. ramosissima. How T. ramosissima copes with extremely low rainfall and a deep groundwater table remains unknown. To answer this, the transpiration and the water sources of T. ramosissima were investigated by the heat balance and oxygen isotopic analysis method, respectively. Our results show that the daily T. ramosissima stem sap flow (SSF) was positively correlated with air temperature (Ta), photosynthetically active radiation (PAR), and the vapor pressure deficit (VPD). We found no significant relationship between the daily SSF and soil moisture in shallow (0–40 cm) and middle (40–160 cm) soil layers. Oxygen isotope results showed that T. ramosissima mainly sources (>90%) water from deep soil moisture (160–400 cm) and groundwater (910 cm). Diurnally, T. ramosissima SSF showed a hysteresis response to variations in PAR, Ta, and VPD, which suggests that transpiration suffers increasingly from water stress with increasing PAR, Ta, and VPD. Our results indicate that PAR, Ta, and VPD are the dominant factors that control T. ramosissima SSF, not precipitation and shallow soil moisture. Deep soil water and groundwater are the primary sources for T. ramosissima in this extremely water-limited environment. These results provide information that is essential for proper water resource management during vegetation restoration and ecological reafforestation in water-limited regions.